2013
DOI: 10.1016/j.expneurol.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Mercaptoacetamide-based class II HDAC inhibitor lowers Aβ levels and improves learning and memory in a mouse model of Alzheimer's disease

Abstract: Histone deacetylase inhibitors (HDACIs) alter gene expression epigenetically by interfering with the normal functions of HDAC. Given their ability to decrease Aβ levels, HDACIs area potential treatment for Alzheimer's disease (AD). However, it is unclear how HDACIs alter Aβ levels. We developed two novel HDAC inhibitors with improved pharmacological properties, such as a longer half-life and greater penetration of the blood-brain barrier: mercaptoacetamide-based class II HDACI (coded as W2) and hydroxamide-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 28 publications
(40 reference statements)
2
91
0
Order By: Relevance
“…7 Furthermore, in a mouse model of AD, the application of HDAC inhibitors attenuates Ab oligomerinduced drebrin loss from dendritic spines, 22 decreases Ab levels, and improves learning and memory. 23 This evidence strongly suggests a critical role of HDAC2 in various aspects of AD pathogeneses, such as the amyloid precursor protein (APP) process, synaptic dysfunction, and memory impairment. The accumulation of HDAC2 also occurs at the beginning at Braak stages I/II, which are characterized by the accumulation of hyperphosphorylated tau protein in the brain, and correlates with cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, in a mouse model of AD, the application of HDAC inhibitors attenuates Ab oligomerinduced drebrin loss from dendritic spines, 22 decreases Ab levels, and improves learning and memory. 23 This evidence strongly suggests a critical role of HDAC2 in various aspects of AD pathogeneses, such as the amyloid precursor protein (APP) process, synaptic dysfunction, and memory impairment. The accumulation of HDAC2 also occurs at the beginning at Braak stages I/II, which are characterized by the accumulation of hyperphosphorylated tau protein in the brain, and correlates with cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the induction of genes implicated in synaptic plasticity, the formation of new dendritic spines, and the increase in pCamKII observed in mice treated with CM-414 may at least partially underlie the restoration of memory in these transgenic mice. Finally, the inhibition of HDAC6 may facilitate the degradation of misfolded proteins, such as Aβ and pTau (Sung et al, 2012;Yu et al, 2013;Zhang et al, 2014). Although different studies have demonstrated that HDACi or PDE5i improved cognitive deficits in animal models of AD, their role on amyloid pathology is controversial (Benito et al, 2015;Cuadrado-Tejedor et al, 2011b;Garcia-Barroso et al, 2013;Puzzo et al, 2009;Qing et al, 2008;Ricobaraza et al, 2009;Rumbaugh et al, 2015;Zhang and Schluesener, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these enzymes have been described as negative regulators of memory consolidation (Guan et al, 2009;McQuown et al, 2011). In contrast, HDAC6 regulates microtubule function and stability via tubulin acetylation (Guan et al, 2009;Hubbert et al, 2002), and dampening HDAC6 activity promotes tau and Aβ clearance (Cook et al, 2012;Sung et al, 2012;Zhang et al, 2014). Notably, HDAC2 and HDAC6 are overexpressed in the cortex and hippocampus of AD patients, although the cause and effect of this upregulation remains unknown (Ding et al, 2008;Graff et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in HDAC6 as a possible therapeutic target in the CNS (d'Ydewalle et al, 2012) has grown considerably following discovery of the key role of this enzyme in aggresome formation (Kawaguchi et al, 2003), pathological evidence for its inclusion in Lewy bodies in Parkinson's disease as well as in glial cytoplasmic inclusions in frontotemporal lobar degeneration with TDP-43 inclusions (Ding et al, 2008), and evidence suggestive of a role in Alzheimer's disease (Govindarajan et al, 2012;Sung et al, 2013;Xiong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%